Submillimeter polarization observation of the protoplanetary disk around HD 142527 - Kataoka, Akimasa; Dullemond, Cornelis; Pohl, Adriana (Arxiv, 2016)
We present the polarization observations toward the circumstellar disk around HD 142527 by using Atacama Large Millimeter/submillimeter Array (ALMA) at the frequency of 343 GHz. The beam size is $0.51 " × 0.44 "$, which corresponds to the spatial resolution of $\sim$ 71 $×$ 62 AU. The polarized intensity displays a ring-like structure with a peak located on the east side with a polarization fraction of $P= 3.26 ± 0.02$ %, which is different from the peak of the continuum emission from the northeast region. The polarized intensity is significantly weaker at the peak of the continuum where $P= 0.220 ± 0.010$ %. The polarization vectors are in the radial direction in the main ring of the polarized intensity, while there are two regions outside at the northwest and northeast areas where the vectors are in the azimuthal direction. If the polarization vectors represent the magnetic field morphology, the polarization vectors indicate the toroidal magnetic field configuration on the main ring and the poloidal fields outside. On the other hand, the flip of the polarization vectors is predicted by the self-scattering of thermal dust emission due to the change of the direction of thermal radiation flux. Therefore, we conclude that self-scattering of thermal dust emission plays a major role in producing polarization at millimeter wavelengths in this protoplanetary disk. Also, this puts a constraint on the maximum grain size to be approximately 150 ${\rm μ m}$ if we assume compact spherical dust grains.